Contested conversions to Islam narratives of religious change in the early modern Ottoman Empire - Krstic, Tijana (Stanford University Press, 2011)
This book explores the role of conversion to Islam in the emergence of the Ottoman Empire, its imperial ideology and Sunni identity, and its relationship with its Muslim and non-Muslim subjects, in the context of the early modern Mediterranean.